2012
DOI: 10.1007/s10461-011-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Network and Other Correlates of HIV Testing: Findings from Male Sex Workers and Other MSM in Shanghai, China

Abstract: Although the Chinese government provides free-of-charge voluntary HIV counseling and testing, HIV testing rates among men who have sex with men (MSM) are reported to be extremely low. This study examines the association of structural and psychosocial factors and social network characteristics with HIV testing behaviors among "money boys" and general MSM in Shanghai. Overall, 28.5% of "money boys" and 50.5% of general MSM had never tested for HIV despite high rates of reported HIV risk behaviors. Factors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 44 publications
12
84
0
Order By: Relevance
“…behaviors [4][5][6] and that they offer emotional support for both HIV-positive as well as HIV-negative MSM. 7 8 Conversely, observations have been made regarding the negative influence of networks with low levels of normative support for safe sex on individual members' involvement in high-risk sexual behaviours.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…behaviors [4][5][6] and that they offer emotional support for both HIV-positive as well as HIV-negative MSM. 7 8 Conversely, observations have been made regarding the negative influence of networks with low levels of normative support for safe sex on individual members' involvement in high-risk sexual behaviours.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…It is precisely the effect of the stigma which explains certain risk behaviors such as the MSW not taking diagnostic tests. A study done in China found that 28.5% of "money boys" had never tested for HIV and factors associated included: not knowing of a testing site, concern about HIV testing confidentiality, being a closeted gay, and having a small social network [29]. Table 1 summarizes studies on effectiveness of HIV prevention programs and findings of the most recent research in this population.…”
Section: Suggested Components That May Be Included In Preventive Progmentioning
confidence: 99%
“…Thus, HIV-positive MSM had low utilization of HIV-related services despite their high risk. 15,22 Studies have suggested that certain socio-demographic characteristics (e.g., being younger, single, or less educated) 23 are associated with lower HIV care utilization rates. Some structural barriers (e.g., public and exposed location for care, inconvenience of clinic hours or venues, confidentiality of disclosure of HIV status, high cost, and lack of real-time provision of counseling) might delay access to and discontinue HIV care utilization.…”
Section: Introductionmentioning
confidence: 99%